Dehidrasi Etanol Menggunakan Zeolit Teraktivasi Irradiasi Lampu Sinar Ultraviolet (UV Light) pada Kolom Fixed Bed - M. Praditia Ansor; Simparmin Br. Ginting; Muhammad Haviz; Darmansyah (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
To obtain ethanol purity >99.5%, an adsorption method using Lampung Natural Zeolite (ZAL) is needed. In order to be used as a zeolite adsorbent, activation must be carried out using UV light lamp irradiation germicidal lamp 254 nm, blacklight lamp 360 nm and insect lamp 546 nm. The results of the BET characteristic test showed that the surface area of ??the non-treated zeolite was 41,331 m2/g, the germicidal lamp was 41,158 m2/g, the black light lamp was 40,399 m2/g and the insect lamp was 38,796 m2/g. The largest total pore volume was obtained from UV germicidal lamp activated zeolite 0.0690 cc/gram and the average pore size was found in insect lamp activated zeolite 35.57. After the activation of the zeolite, pellets were formed using a binder from wheat flour with a composition of 35% by weight of zeolite, then the zeolite was calcined to remove the binder that was still attached and opened the pores that were closed by the binder. The results obtained were dehydrated ethanol to increase purity using zeolite activated by UV germicidal lamp 98.69% v/v for 45 minutes, blacklight and insect lamp 98.69% v/v for 55 minutes.